2005
DOI: 10.1021/ac050912p
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Determination of 234U/238U Ratio with Improved Precision

Abstract: A new mass spectrometric method is proposed for measurement of 234U/238U ratio with a single Daly electron multiplier detector using the general peak jump method. The method is based on precise measurement of the 235U/238U ratio and 234U/235U ratio, which are used to calculate the 234U/238U ratio using the equation 234U/238U = 235U/238U x 234U/235U. The results show a significant improvement, i.e., more than 35 times better precision in measuring the (234)U/(238)U ratio with this method (sigma = 2.9 x 10(-8)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Using the environmental performance index as an indicator of environmental quality for a large sample of countries, Lisciandra and Migliardo [12] found that increases in levels of corruption reduce environmental quality. Other studies also found a positive relationship between corruption and environmental damage as in Rehman et al [47] (South Asian countries) and Sinha et al [2] (BRICS). Some studies found significant results at high quantiles as in Luqman et al [27] for the case of Pakistan, while others did not find any significant results, as in Azam and Khan [6] for the case of Malaysia, Indonesia, and Thailand, or Haldar and Sethi [10] for a sample of developing countries.…”
Section: Discussionmentioning
confidence: 80%
“…Using the environmental performance index as an indicator of environmental quality for a large sample of countries, Lisciandra and Migliardo [12] found that increases in levels of corruption reduce environmental quality. Other studies also found a positive relationship between corruption and environmental damage as in Rehman et al [47] (South Asian countries) and Sinha et al [2] (BRICS). Some studies found significant results at high quantiles as in Luqman et al [27] for the case of Pakistan, while others did not find any significant results, as in Azam and Khan [6] for the case of Malaysia, Indonesia, and Thailand, or Haldar and Sethi [10] for a sample of developing countries.…”
Section: Discussionmentioning
confidence: 80%
“…Lipid peroxidation (LPO) : Lipid peroxidation was estimated by the Thio‐barbituric acid (TBA) method. The equal quantity (1 ml) of liver homogenate and trichloro acetic acid was centrifuged at 2000 rpm for 10 min, to the supernatant (1 ml) added same amount (1 ml) of thiobarbituric acid (0.67 %) and warm for 10 min, cooled and diluted with distilled water (1 ml) and read absorbance at 535 nm [15] Badgujar Prarabdh.…”
Section: Methodsmentioning
confidence: 99%
“… Lipid peroxidation (LPO) : Lipid peroxidation was estimated by the Thio‐barbituric acid (TBA) method. The equal quantity (1 ml) of liver homogenate and trichloro acetic acid was centrifuged at 2000 rpm for 10 min, to the supernatant (1 ml) added same amount (1 ml) of thiobarbituric acid (0.67 %) and warm for 10 min, cooled and diluted with distilled water (1 ml) and read absorbance at 535 nm [15] Badgujar Prarabdh. Superoxide Dismutase (SOD) : The reaction mixture consists of homogenate (10 μl), MTT (30 μl), PBS (640 μl) and pyrogallol (70 μl), incubated for 10 min at room temperature. Add equal amount of DMSO (750 μl) and the absorbance was measured at 570 nm [16] …”
Section: Methodsmentioning
confidence: 99%
“…While FT‐CARS flow cytometry and dual‐membrane push–pull cell sorting have been reported previously, [ 32,34,35 ] their integration in this machine required significant development, particularly for real‐time spectral processing. This demonstration also distinguishes RACS and FACS; while microalgal polysaccharide granules continue to garner interest for medical, [ 36 ] biofuel, [ 37,38 ] and bioplastic applications, [ 39 ] they remain difficult to stain and thus detect in FACS, highlighting the suitability of our RACS machine for unmet bioengineering applications.…”
Section: Introductionmentioning
confidence: 96%